2016
DOI: 10.21162/pakjas/16.5573
|View full text |Cite
|
Sign up to set email alerts
|

Toxicopathological and Serum Biochemical Alterations Induced by Ochratoxin a in Broiler Chicks and Their Amelioration by Locally Available Bentonite Clay

Abstract: Ochratoxin A (OTA), a potent carcinogen, poses a great threat to the lives of poultry, animals and humans. It causes nephrotoxicity, immunosuppression, mutagenicity and teratogenicity in birds. Bentonite clay, belonging to the subclass of aluminosilicates, has the ability to adsorb different molecules and can efficiently adsorb several mycotoxins too. The present study was designed to evaluate the ameliorative effects of locally available bentonite clay against OTA induced toxicopathological and serum biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…The OTA resulted in severe economic losses in the poultry industry due to its deleterious effects on the growth rate, feeding efficiency and high mortality [ 9 ]. Once a mycotoxin enters the food chain, its 100% eradication is not possible [ 10 ]. Previous literature regarding their toxicity testing revealed that LD 50 (Oral median lethal dose) values in turkeys, quails and ducks and chicken were 5.9, 16.5, 0.5 and 2 to 4 mg/kg of body weight, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The OTA resulted in severe economic losses in the poultry industry due to its deleterious effects on the growth rate, feeding efficiency and high mortality [ 9 ]. Once a mycotoxin enters the food chain, its 100% eradication is not possible [ 10 ]. Previous literature regarding their toxicity testing revealed that LD 50 (Oral median lethal dose) values in turkeys, quails and ducks and chicken were 5.9, 16.5, 0.5 and 2 to 4 mg/kg of body weight, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of mycotoxins surveys have been carried out to investigate the worldwide occurrence of mycotoxins in feed materials such as wheat, maize, soybean meal, and dried distillers' grains (Monbaliu et al 2010;Rodrigues and Naehrer 2012;Streit et al 2013;Kosicki et al 2016). The toxic effects of mycotoxin on animal health is termed mycotoxicosis, the degree of toxicity depends on the type of mycotoxins, level ingested, exposure time, breed, age, sex, health status of animal, and other stress factors (Zaki 2012;Khatoon 2016;Ostry et al 2016;Dellafiora and Dall'Asta 2017). To counteract mycotoxicosis in farm animals, the European Commission (EC) regulation on additives for use in animal nutrition was amended and a new regulation (EC No 386/ 2009) in the category of technological feed additives defines a new functional group of feed additives as "substances for reduction of the contamination of feed by mycotoxins: substances that can suppress or reduce the absorption, promote the excretion of mycotoxins or modify their mode of action."…”
Section: Introductionmentioning
confidence: 99%
“…Diseases caused by secondary metabolites are called mycotoxicoses [81]. The degree of toxicity that these compounds exert on the animal's body depends primarily on the type of mycotoxin, amount, duration of exposure, overall health of the animal, sex, age, race, and other factors [82][83][84][85].…”
Section: Impact On Animal Healthmentioning
confidence: 99%